SYNTHESIS OF MESOPOROUS ALUMINA TEMPLATED BY MALTOSA FOR SACCHARIDE SEPARATION - ASEP SYAMSUL ARIFIN (NIM : 10508056); Pembimbing : Dr. Suryo Gandasasmita
Mesoporous alumina has been synthesized by using maltose as a template for separation of a mixture of maltose and starch. It was found that pH affects the pore diameter of material. The greatest pore diameter (6.25 nm) was obtained when the pH of synthesis solution was 6. Separation was performed on the basis of the chromatography principle using mesoporous alumina as stationary phase and water as mobile phase. A mixture of maltose and starch could be separated where the second fraction was eluted having the highest maltose concentration of 3400 ppm and the starch was adsorbed in separating material until last fraction was taken. However, the synthesized mesoporous alumina was found not proper as a separating media for a mixture of disaccharides. A mixture of maltose and sucrose cannot be separated by such a material because both were eluted at the same time.